ANALISIS PERLINDUNGAN HUKUM BAGI KONSUMEN KREDIT MACET : PERSPEKTIF PERJANJIAN FIDUSIA: Perlindungan Hukum, Kredit Macet dan Perjanjian Fidusia - Khasanah, Uswatun (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
Fiduciary agreements are a form of binding guarantees that are often used in credit transactions, especially in financing institutions. However, in practice, there are often cases of bad loans that have an impact on the risk of withdrawal of the collateral object by creditors without considering the rights of consumers as debtors. This study aims to analyze the legal protection available to consumers in bad credit situations, as well as how to apply the principles of consumer protection in fiduciary agreements in Indonesia. This research is expected to provide insight into the importance of legal protection for consumers and encourage related parties to create a better protection system.